The effect of mobile problem-based science dictionary application dicscience pbl towards students' mastery of scientific terms and critical thinking - Ismail, Nurul Syazwani (2017)
The Malaysian Ministry of Education has stated that the main objective of education is to produce students who possess higher order thinking skills (HOTS). For this purpose, students' engagement in teaching and learning is of great concern. In the initiatives taken to help them towards achieving a better level of thinking, teaching and learning resource is one of the important factors to be considered to effectively get them engaged in active learning. One of the resource alternatives that can be used is to integrate technology into teaching and learning. Mobile technology is one of the latest technologies which has the potential to be leveraged in realizing the intended objective. Thus, this paper discussed the ways, the development of Mobile Problem-Based Science Dictionary (DicScience PBL), was able to help students not only in mastering scientific terms but also helping them to think more critically. By combining constructivism design principle and problem based learning (PBL), the PBL processes and critical thinking elements in the development phase, this application was able to give positive effect to the students' mastery in scientific terms (M=48.56, p<0.05) and their critical thinking (M=22.0, p<0.05) and analyses of the results had found a significant relationship between mastery of the scientific terms and students' critical thinking (r=0.764, p<0.05). Results from the interview data also found that the characteristics in the DicScience PBL application were not only helpful to get the students engaged in the learning process, but also to get them motivated to think in higher orders.